2021
DOI: 10.1002/pits.22573
|View full text |Cite
|
Sign up to set email alerts
|

The role of infant and early childhood mental health consultation in reducing racial and gender relational and discipline disparities between Black and white preschoolers

Abstract: This study presents findings from an Infant and Early Childhood Mental Health Consultation (IECMHC) initiative in Arizona called Smart Support. The IECMHC used an early childhood mental health consultation model as an early childhood education intervention to address the needs of preschoolers with challenging behaviors. Disparities in teacher‐child relationships and discipline are some of the most persistent racial disparities impacting young Black children. The goal of IECMHC is to facilitate teachers' skills… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 51 publications
0
8
0
Order By: Relevance
“…Shivers et al. (2022) also measured expulsion risk and found that it decreased more strongly for Black boys than white boys over the course of a 12‐month IECMHC program. No papers reviewed included family outcomes as part of their design.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Shivers et al. (2022) also measured expulsion risk and found that it decreased more strongly for Black boys than white boys over the course of a 12‐month IECMHC program. No papers reviewed included family outcomes as part of their design.…”
Section: Resultsmentioning
confidence: 99%
“…A small number of empirical papers published after 2020 address structural factors as they are encountered in IMH and IECMH work. One study reviewed (Shivers et al., 2022) explicitly addressed structural racial inequality. In their quantitative, longitudinal study, the authors examined whether IECMH consultation could impact early childhood teacher perceptions of the behavior of young Black boys, given the implicit biases which are thought to contribute to disciplinary disparities in educational settings for this population.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…For example, anxiety might look different in African American children and be mistaken for problem behaviors. When these errors occur, children do not receive adequate care, and often mental or behavioral health symptoms get worse resulting in poor academic, social, and emotional outcomes, which means early intervention is imperative (Shivers et al., 2021). Researchers should further examine why African American children are disproportionately diagnosed with behavioral problems, as evidenced by the current and existing research on this topic.…”
Section: Discussionmentioning
confidence: 99%